Interdependency patterns of potential seaport risk factors in relation to supply chain disruption in Indonesia - Muhammad Reza Do. Bagus; Shinya Hanaoka (Journal of Shipping and Trade (JST), 2023)
As an integral part of the global supply chain network, Indonesian supply chain entities should understand conditional seaport risk factors that could lead to seaport threats that affect supply chain continuity. This study aims to provide a procedure for evaluating the interdependencies, implications, and correlations among various seaport risk factors for supply chain threats, specifically by investigating current practices in the developed economic region of Indonesian seaport operations. The study uses a rough set method to solve feature selection problems and multivariate analysis of variance to assess the correlation between dependent and independent variables. We find 39 conditional seaport risk factors that are potentially influenced by about 21 dependent factors related to seaport-fulcrum supply chain entities. Furthermore, threats from the planning process, infrastructure, seaport service process, distribution process, financial costs of nuclear enterprises and security existed and affluent highest potential risk in Indonesia.
Keywords: 650; Association rule mining; Genetic algorithm; Interdependency risk analysis; Rule rough set theory; Seaport risk factors